Does Where You Stand Depend on Where You Sit? Tithing Donations and Self-Serving Beliefs - Dahl, Gordon B; Ransom, Michael R (American Economic Review, 1999)
Economists and psychologists argue that individuals skew personal beliefs to accord with their own interests. To test for the presence of self-serving beliefs, we surveyed 1,200 members of the Mormon Church about tithing. A tithe is a voluntary contribution equal to 10 percent of income. Since respondents must decide privately what income items to tithe, we observe how the income definition depends on an individual's religious and financial incentives. We find surprisingly little evidence that an individual's financial situation influences beliefs about what counts as income for the tithe. However, ambiguity increases the role for self-serving biases. (JEL A12, D63)